2014
DOI: 10.3892/ol.2014.2625
|View full text |Cite
|
Sign up to set email alerts
|

Synchronous primary cancers of the thyroid and breast: A case report and review of the literature

Abstract: The current report presents the case of a 41-year-old female exhibiting synchronous primary cancers of the thyroid and breast. Pathological examination of a tissue sample following biopsy identified papillary carcinoma of the thyroid and invasive ductal carcinoma of the breast to provide a definitive diagnosis of synchronous primary tumors. The patient underwent a modified radical mastectomy and total thyroidectomy. Following regular adjuvant chemotherapy with cyclophosphamide (800 mg), doxorubicin (100 mg) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…A recent study showed that radiotherapy for breast cancer is significantly associated with an increased risk of a second nonbreast cancer both overall and in organs adjacent to the previous treatment fields [ 22 ]. Consistent with previous studies, in our study, synchronous primary cancers of the thyroid and breast were common findings [ 15 ]. A recent study showed that 131 I therapy for thyroid cancer did not increase the incidence or recurrence rate of breast cancer [ 23 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…A recent study showed that radiotherapy for breast cancer is significantly associated with an increased risk of a second nonbreast cancer both overall and in organs adjacent to the previous treatment fields [ 22 ]. Consistent with previous studies, in our study, synchronous primary cancers of the thyroid and breast were common findings [ 15 ]. A recent study showed that 131 I therapy for thyroid cancer did not increase the incidence or recurrence rate of breast cancer [ 23 ].…”
Section: Discussionsupporting
confidence: 93%
“…Our data illustrated that SPM in patients with well-differentiated thyroid carcinoma presented with a more advanced TNM stage and higher thyroid cancer-specific and overall mortality compared to patients without SPM. In a recent study, breast cancer was the most common synchronous or antecedent nonthyroidal malignancy in women with well-differentiated thyroid carcinoma [ 14 , 15 ]. SPM of digestive system, oral cavity, or pharynx origin was more common in this area than in Western countries [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is hypothesized that the synchronous occurrence of two tumors may be a result of a mutagenic trigger that causes independent genetic events7 and that metachronous tumors may be due to persisting effects of genetic and behavioral risk factors 7. It is possible the thyroid gland may be activated by prior hormone-secreting cancers with overstimulation in a reactive autoimmune environment, as hypothesized by Sisti et al8 Furthermore, a history of thyroid cancer is associated with the increased risk of developing breast cancer, and several studies have evaluated the thyroid hormone and proposed mechanisms for activation of the associated oncogene 9. The most likely explanation for synchronous cancers in the present case seems to be a sporadic thyroid cancer on a background of genetic cancer predisposition.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, there are genetic syndromes such as the Cowden syndrome or the Cowden-like syndrome, in which breast and thyroid cancers are associated (93). It is therefore not surprising that there are several case reports of breast and thyroid MPMNs, both synchronous (48,94) and metachronous (10,64).…”
Section: Breast Cancer and Gynecological Tumorsmentioning
confidence: 99%